Critical Role of Astrocytic Polyamine and GABA Metabolism in Epileptogenesis - Kovács, Zsolt; Skatchkov, Serguei N.; Veh, Rüdiger W.; Szabó, Zsolt; Németh, Krisztina; Szabó, Pál T.; Kardos, Julianna; Héja, László (Frontiers in Cellular Neuroscience, 2022)
Accumulating evidence indicate that astrocytes are essential players of the excitatory and inhibitory signaling during normal and epileptiform activity via uptake and release of gliotransmitters, ions and other substances. Polyamines can be regarded as gliotransmitters since they are almost exclusively stored in astrocytes and can be released by various mechanisms. The polyamine putrescine (PUT) is utilized to synthesize GABA which can also be released from astrocytes and provide tonic inhibition on neurons. The polyamine spermine (SPM), synthesized form PUT through spermidine (SPD) is known to unblock astrocytic Cx43 gap junction channels and therefore facilitate astrocytic synchronization. In addition, SPM released from astrocytes may also modulate neuronal NMDA, AMPA and kainate receptors. As a consequence, astrocytic polyamines possess the capability to significantly modulate epileptiform activity. Here we investigated different steps in polyamine metabolism and coupled GABA release to assess their potential to control seizure generation and maintenance in two different epilepsy models: the low-[Mg2+] model of temporal lobe epilepsy in vitro and in the WAG/Rij rat model of absence epilepsy in vivo. We show that SPM is a gliotransmitter that is released from astrocytes and significantly contributes to network excitation. Importantly, we found that inhibition of SPD synthesis completely prevented seizure generation in WAG/Rij rats. We hypothesize that this anti-epileptic effect is attributed to the subsequent enhancement of PUT to GABA conversion in astrocytes, leading to GABA release through GAT-2/3 transporters. This interpretation is supported by the observation that anti-epileptic potential of the FDA-approved drug levetiracetam can be diminished by specifically blocking astrocytic GAT-2/3 with SNAP-5114, suggesting that levetiracetam exerts its effect by increasing surface expression of GAT-2/3. Our findings conclusively suggest that the major pathway through which astrocytic polyamines contribute to epileptiform activity is the production of GABA. Modulation of astrocytic polyamine levels, therefore, may serve for a more effective anti-epileptic drug development in the future.